Social environment and forms of governance: Monetary and non-monetary punishment and the role of emotions - Marianna Bicskei; Matthias Lankau; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
The question to what extent social environment affects how individuals govern their groups, has received no special academic attention, yet. Within the framework of a ten-period public goods experi&ment we analyse how social identity affects subjects' choice of punishment: They may either sanction group members by monetary and/or by non-monetary sanctions bearing differentconsequences on welfare. What is more, we are also the first to address how emotions influence the effectiveness of punishment in terms of maintaining contributions. Our results show that under the threat of both punishments identity-heterogeneous (out-) groups tend to contribute more to the public good than identity-homogenous (in-) groups. Nevertheless, subjects of out-groups are more likely to govern their group via monetary, in-group members rather via non-monetary punishment. What is more, we demonstrate that emotions of guilt and anger differently affect subsequent contributions dependent on the social environment.
Keywords: 330; public goods; social identity; monetary and non-monetary peer-punishment; emotions